Antibacterial and anti-biofilm activity of diarylureas against Enterococcus faecium by suppressing the gene expression of peptidoglycan hydrolases and adherence - Xie, Yunfeng; Wang, Lei; Yang, Yang; Zha, Liang; Zhang, Jiazhen; Rong, Kuanrong; Tang, Wenjian; Zhang, Jing (Frontiers in Microbiology, 2022)
Enterococcus faecium (E. faecium) is a clinical multidrug-resistant pathogen causing life-threatening infection, which makes it important to discover antibacterial agents with novel scaffolds and unique mechanism. In this study, the diarylurea scaffold was found to have potent antibacterial effect on E. faecium. Diarylurea ZJ-2 with benign drug-like property exhibited potent antibacterial and anti-biofilm activity through inhibiting the genes expression of NlpC/p60 hydrolase-secreted antigen A (sagA) and autolysins (atlA), down-regulating the expression of Fsr quorum-sensing (QS) regulatory genes (fsrA, fsrB and fsrC), virulence genes (sprE, gelE) and biofilm adherence related genes (agg and esp) against E. faecium. Moreover, ZJ-2 can be docked into SagA to inhibit daughter cell separation. In a mouse model of abdominal infection, ZJ-2 decreased the bacterial load and the level of IL-6 and TNF-α in a time-dependent manner. Overall, these findings indicated that diarylurea ZJ-2 has the potential to be developed as a therapeutic agent to treat drug-resistant enterococci and biofilm-related infections.